Asymptomatic Hyperuricemia. (25th March 2016) - Hosoya, Tatsuo; Nishio, Shinichiro
Abstract : According to recent study, hyperuricemia is not only a basic pathology of gout, but has been found that it is intimately related to the development and progress of hypertension, chronic renal disease (CKD), cardiovascular disease, and stroke. This means that hypertension, CKD and cardiovascular disease are caused by the direct effect (pro‐oxidant effect) of urate without going through urate crystal deposition. If the above issues can be indicated as clear evidence by treatment of interventional clinical trials, it can be thought that the treatment strategy for hyperuricemia to prevent organ damage will see substantial progress.